Describing adverse events in Swiss hospitalized oncology patients using the Global Trigger Tool. Issue 2 (12th May 2020) - Gerber, Anne; Da Silva Lopes, André; Szüts, Natacha; Simon, Michael; Ribordy‐Baudat, Viviane; Ebneter, Andreas; Perrinjaquet, Claire; Gaignard, Marie‐Estelle; Nicodet, Delphine; Betticher, Daniel; Bula, Grégoire; Cote, Maxime; et al.
Abstract: Background and aims: The occurrence rate of adverse events (AEs) related to care among hospitalized oncology patients in Switzerland remains unknown. The primary objective of this study was to describe, for the first time, the occurrence rate, type, severity of harm, and preventability of AEs related to care, reported in health records of hospitalized hematological and solid‐tumor cancer patients in three Swiss hospitals. Methods: Using an adapted version of the validated Global Trigger Tool (GTT) from the Institute for Healthcare Improvement, we conducted a retrospective record review of patients discharged from oncology units over a 6‐week period during 2018. Our convenience sample included all records from adult patients (≥18 years of age), diagnosed with cancer, and hospitalized (>24 hours). Per the GTT method, two trained nurses independently assessed patient records to identify AEs using triggers, and physicians from the included units analyzed the consensus of the two nurses. Together, they assessed the severity and preventability of each AE. Results: From the sample of 224 reviewed records, we identified 661 triggers and 169 AEs in 94 of them (42%). Pain related to care was the most frequent AE (n = 29), followed by constipation (n = 17). AEs rates were 75.4 per 100 admissions and 106.6 per 1000 patient days. Most of the identified AEs (78%) caused temporary harm to the patient and required an intervention. Among AEs during hospitalization (n = 125), 76 (61%) were considered not preventable, 28 (22%) preventable, and 21 (17%) undetermined. Conclusion: About half of the hospitalized oncology patients suffered from at least one AE related to care during their hospitalization. Pain, constipation, and nosocomial infections were the most frequent AEs. It is, therefore, essential to identify AEs to guide future clinical practice initiatives to ensure patient safety.